Avaliação da capacidade inibidora da corrosão de aminas a partir do aspecto molecular - Lima, Eduardo Galdino Alves (Universidade Federal de São Carlos, 2015)
This project aims the evaluation of some amines as corrosion inhibitors in carbon steel alloys amid hydrochloric acid (pickling bath). For that, analytical aspects of corrosion process has been considered and the results were interpreted considering the molecular interaction with the metal surface.
Assessment of amines as corrosion inhibition capacity from a molecular aspect
Keywords: Corrosão; Inibidores; Aminas; Aço carbono; Meio ácido clorídrico; Corrosion inhibitors; Amines; Carbon steel; Pickling process; CIENCIAS EXATAS E DA TERRA